2015
DOI: 10.1098/rstb.2014.0299
|View full text |Cite
|
Sign up to set email alerts
|

The tortoise or the hare? Impacts of within-host dynamics on transmission success of arthropod-borne viruses

Abstract: One contribution of 17 to a theme issue 'Within-host dynamics of infection: from ecological insights to evolutionary predictions'. Arthropod-borne viruses (arboviruses) are maintained in a cycle of alternating transmission between vertebrate hosts and arthropod vectors. Arboviruses possess RNA genomes capable of rapid diversification and adaptation, and the between-host trade-offs inherent to host alternation impose well-documented constraints on arbovirus evolution. Here, we investigate the less well-studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
59
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 100 publications
6
59
0
Order By: Relevance
“…Our model extends, to our knowledge, the only previous dynamic model of mosquito-borne viruses in non-human primate hosts [54, 55]. While our previous modeling study was focused on sylvatic DENV [54], the strong similarities between sylvatic DENV and sylvatic ZIKV transmission cycle make the model a good fit for both viruses.…”
Section: Establishing a Sylvatic Zikv Cyclementioning
confidence: 68%
See 1 more Smart Citation
“…Our model extends, to our knowledge, the only previous dynamic model of mosquito-borne viruses in non-human primate hosts [54, 55]. While our previous modeling study was focused on sylvatic DENV [54], the strong similarities between sylvatic DENV and sylvatic ZIKV transmission cycle make the model a good fit for both viruses.…”
Section: Establishing a Sylvatic Zikv Cyclementioning
confidence: 68%
“…These studies should (i) incorporate multiple species of New World primates, (ii) compare virus dynamics resulting from virus delivery by needle versus mosquito vector, (iii) monitor intra-host infection dynamics over a duration that exceeds that currently documented for viremia in humans, (iv) utilize both culture and direct mosquito feeding to detect viremia, and (v) monitor pathogenesis of the virus with a focus on potential impact of the virus on survival [55]. …”
Section: Discussionmentioning
confidence: 99%
“…Another major factor in vector transmission is the amount of virus inoculated in the saliva, which can affect pathogenesis ( 21 ); this value is critical for determining realistic animal model doses. We found saliva titers of up to 4 log 10 FFU per collection, with the following mean ±SD log 10 FFU/collection for each mosquito–virus strain combination: Salvador mosquitoes, DAK AR 41525: 2.49 ±2.93; DR mosquitoes, DAK AR 41525: 2.72 ±3.26; DR mosquitoes, MEX1–7: 2.30 ±2.35; RGV mosquitoes, DAK AR: 2.20 ±1.96; Salvador mosquitoes, FSS 13025 infected through a murine blood meal: 2.77 ±3.00.…”
Section: Discussionmentioning
confidence: 99%
“…Because geographically disparate populations of this species can vary in their susceptibility to flaviviruses ( 20 ), including Zika virus ( 15 ), we tested populations from 3 at-risk sites in the Americas—Brazil (Salvador), the Caribbean (Dominican Republic [DR]), and the United States (Rio Grande Valley [RGV], Texas)—with Zika virus strains from Senegal (DAK AR 41525), Cambodia (FSS 13025), and a 2015 Mexico outbreak (MEX1–7) ( 14 ). We also estimated the extrinsic incubation period (EIP) and viral titers in mosquito saliva and characterized differences in infection and dissemination between artificial and viremic blood meals ( 21 ). …”
mentioning
confidence: 99%
“…also found that the temporality of transmission from non-human primates was sometimes more impactful than the magnitude of the viremia leading to transmission to the mosquito [48]. They proposed a "tortoise-or-the-hare" (TotH) model to describe this relationship between arboviral viremia profiles in non-human primates and the predicted transmission success to vectors, showing that the strategy of "slow and steady" viremia -lower levels for longer periods -resulted in higher predicted transmission success of arboviruses [48]. Here again we invoke the TotH model to describe the complimentary side of the vector-borne pathogen transmission cycles, in the direction of vector-to-vertebrate.…”
Section: Discussionmentioning
confidence: 95%